Cropping systems strategy for effective management of Fusarium wilt in safflower - Nageswara Rao V; Sastry RK; Craufurd, Peter Q.; Meinke, Holger; Parsons, D.; Rego TJ; Rathore A (Elsevier, 2014)
In many parts of India intensive cultivation of safflower on Vertisols appears to have aggravated the problem of Fusarium wilt in safflower due to the soil borne fungus, Fusarium oxysporum Schlecht f. sp. carthami Klisiwiez and Houstan (FOC). In a long-term field experiment at Patancheru, India, we evaluated four diverse dryland cropping systems that each included safflower for their effectiveness in controlling Fusarium wilt in safflower. Sorghum (rainy season crop) and safflower (post-rainy season crop) were grown every alternate year as a two-year rotation with: (1) sorghum intercropped with pigeonpea (S/PP − S + SF); (2) cowpea intercropped with pigeonpea (C/PP − S + SF); (3) sorghum followed by chickpea (S + CP − S + SF); (4) sorghum followed by safflower (S + SF − S + SF). Continuous sorghum and safflower (S + SF − S + SF) had higher Fusarium wilt incidence of fully wilted safflower plants (31%) and a larger build-up of Fusarium propagules (1728 cfu g−1 of soil) than other cropping systems. The inclusion of a legume such as chickpea in the rotation (S + CP − S + SF) reduced wilt incidence (7% fully wilted plants) and the level of inoculum in the soil to about 800 cfu g−1. There was a significant increase in safflower seed yield and biomass yield (883 and 1733 kg ha−1, respectively) in the S + CP − S + SF rotation compared with the S + SF − S + SF rotation (605 and 1323 kg ha−1, respectively). Nitrogen application at rates of 0 to 120 kg N ha−1 had no effect on wilt incidence in safflower, but increased seed and biomass yield significantly. Intercrop rotations (S/PP − S + SF and C/PP − S + SF) were less effective to manage the Fusarium wilt. The Area Under Disease Progress Curve (AUDPC) was almost 10 times higher in the S + SF − S + SF rotation (2842) compared with the S + CP − S + SF rotation (297). Wilt progress throughout the season in all four systems was linear, with significant differences in intercepts and rates of disease progress among cropping systems; the rate of disease progress was significantly greater in the S + SF − S + SF rotation compared with the other three systems, which were similar. There was also a strong linear relationship between wilt incidence and the number of Fusarium propagules in the soil; regressions had the same slope but different intercepts in each system. There was no relationship between wilt incidence and seed yield; nitrogen had the largest effect on yields. A break from safflower cultivation for one year in the post-rainy season by growing chickpea as a sequential crop after sorghum, or as an intercrop with pigeonpea and sorghum, combined with higher rates of nitrogen application to safflower appears to be an effective strategy for reducing Fusarium populations and sustaining safflower yield.